Design of a Fixed Asset Inventory System at Bank BRI Branch Offices Using the Waterfall Method - Adriansyah Muliawan; Apriansya; Dedi Haryanto (JURNAL TEKNOLOGI DAN OPEN SOURCE, 2025)
Bank Rakyat Indonesia (BRI) is one of the largest state-owned banks in Indonesia with branch offices distributed across various regions, including the BRI 16 Ilir Branch Office located in the central trade area of Palembang City. This branch plays a strategic role in providing banking services such as financial transactions, account opening, and People’s Business Credit (KUR). Based on initial observations, the management of fixed assets at the BRI 16 Ilir Branch Office is still conducted conventionally using physical documents and separate digital spreadsheets. This condition often causes data duplication, delays in updating asset information, inconsistencies between administrative records and physical assets, and difficulties in auditing and monitoring asset conditions. The absence of an integrated system also hampers maintenance planning and asset disposal processes. Therefore, this study aims to develop a web-based inventory information system as an effective solution to improve asset management efficiency and accuracy. The system is designed to record asset data in real time based on category, location, and usage status, and to provide comprehensive monitoring and reporting features. The development process adopts the Waterfall method due to its structured, linear, and well-documented approach. The results are expected to support better asset management practices and contribute to academic references in banking information systems.